Talk-in-interaction of a Malaysian english speaking autistic child during joint comprehension activities - Rosli, Muhammad Nazrin (2019)
Talk-In-Interaction involves the pragmatic knowledge governing the basic aspects of conversation such as organization of turn taking, organization of sequences and organization of repair. Such pragmatic knowledge has been found to be deficient in autistic children and it is evident in their discourse. Studies have shown that children with Autistic Spectrum Disorder (ASD) often find difficulty in discourse references which stems from atypical features of autistic language, namely – pronoun atypicality, pragmatic deficit and echolalia. These atypical features construes interaction between ASD children and their interlocutors resulting in miscommunication of sorts. Activities that require supervision and direction from an interlocutor becomes constrained and require more time including use of specific communication strategies in assisting ASD children. In the case of joint comprehension activities, comprehension in the children’s interaction is the basic fundamental requirement in ensuring coherence and compliance during communication. This case study draws on Kasher’s (1991) theoretical model, under which the autistic core impairments are described in terms of the knowledge required for various pragmatic functions which are analysed through discourse analysis in identifying patterns of communication that involves the language atypicalities mentioned. While studies related to ASD are largely conducted quantitatively, this study incorporated a case study methodology involving a Malaysian English speaking ASD child, to analyse the conversational interactions between the subject and the interlocutor during joint comprehension activities. The study also analyses the perlocutionary effects elicited from directive speech acts since children with autism are reported to produce more feedback during interaction and comprehend directive speech acts better than speech acts that facilitate shared understanding such as representatives and expressive(s).This was also observed to be the case with the subject of the study. The data of the case study was collected through audio/video recordings, and cross-referenced with observations during the joint comprehension activities, as well as interviews with the parents and teacher. The definitions and classifications of the disorder were reviewed from the first description by Kanner (1943) and the Theory of Mind (Leslie, 1987) interpretation of the core impairments in Autism, to the current 5th Diagnostic and Statistical Manual of Mental Disorders (DSM-V, 2013) classifications. Many patterns of communication arose from the use of the atypical language features present; some of which impede, while some was shown to support interaction. It was found that specific communication skills among special needs facilitators have implications for communication in English where meaningful interactions can be formed with the subject, and possibly other Autistic children. It could help to create awareness among educators to establish special needs education guide/text/study/books for the field of special needs education, especially in Malaysia.